Analysis of Risk Factors for Incisional Hernias and its Management - Paudel, S R; Neupane, B R; Gurung, N V; Acharya, A; Chapagain, A; Shrestha, S; Gurung, A; Shrestha, D (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: Incisional hernia is a common problem after abdominal surgery. Patients present with pain, swelling and intestinal obstruction. It may be repaired by either anatomical suturing or mesh repair. Methods: It is a prospective observational study conducted in Western Regional Hospital and Fewa City Hospital, Pokhara from 2013 to 2016. A total of consecutive 100 patients admitted in these hospitals during the study period were included. Results: Incisional hernia is more common in females (M : F = 1 : 3.8), and in 30 - 50 years age group (60%). Major risk factors were wound infection (30%), overweight (25%), and postoperative cough (10%). It is found to be more associated with gynecological (65%), than gastrointestinal operations, and more so with lower abdominal midline incision (65%). It is found to occur mostly within one year (60%) of primary surgery than later. Even 24% of the patients had first symptom within six months. Mesh repair (92%) was the preferred standard surgical treatment for incisional hernia. Conclusion: Overweight females of age range between 30 - 50 years with history of gynecological operations by lower abdominal midline incision are more prone to develop incisional hernia. This incidence increases when there is wound infection. Mesh repair is the choice of operation for incisional hernia. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 16-20